Antibiotics for otitis media with effusion in children - van Zon, Alice; van der Heijden, Geert J; van Dongen, Thijs M A; Burton, Martin J; Schilder, Anne G M (Cochrane database of systematic reviews, 2012)
Otitis media with effusion (OME) is characterised by an accumulation of fluid in the middle ear behind an intact tympanic membrane, without the symptoms or signs of acute infection. In approximately one in three children with OME, however, a bacterial pathogen is identified in the middle ear fluid. In most cases, OME causes mild hearing impairment of short duration. When experienced in early life and when episodes of (bilateral) OME persist or recur, the associated hearing loss may be significant and have a negative impact on speech development and behaviour. Since most cases of OME will resolve spontaneously, only children with persistent middle ear effusion and associated hearing loss potentially require treatment. Previous Cochrane reviews have focused on the effectiveness of ventilation tube insertion, adenoidectomy, autoinflation, antihistamines, decongestants, and oral and topical intranasal steroids in OME. This review focuses on the effectiveness of antibiotics in children with OME. To assess the effects of antibiotics in children up to 18 years with OME. We searched the Cochrane Ear, Nose and Throat Disorders Group Trials Register; the Cochrane Central Register of Controlled Trials (CENTRAL); PubMed; EMBASE; CINAHL; Web of Science; BIOSIS Previews; Cambridge Scientific Abstracts; ICTRP and additional sources for published and unpublished trials. The date of the search was 22 February 2012. Randomised controlled trials comparing oral antibiotics with placebo, no treatment or therapy of unproven effectiveness. Our primary outcome was complete resolution of OME at two to three months. Secondary outcomes included resolution of OME at other time points, hearing, language and speech, ventilation tube insertion and adverse effects. Two authors independently extracted data using standardised data extraction forms and assessed the quality of the included studies using the Cochrane 'Risk of bias' tool. We presented dichotomous results as risk differences as well as risk ratios, with their 95% confidence intervals. If heterogeneity was greater than 75% we did not pool data. We included 23 studies (3027 children) covering a range of antibiotics, participants, outcome measures and time points of evaluation. Overall, we assessed the studies as generally being at low risk of bias.Our primary outcome was complete resolution of OME at two to three months. The differences (improvement) in the proportion of children having such resolution (risk difference (RD)) in the five individual included studies ranged from 1% (RD 0.01, 95% CI -0.11 to 0.12; not significant) to 45% (RD 0.45, 95% CI 0.25 to 0.65). Results from these studies could not be pooled due to clinical and statistical heterogeneity.Pooled analysis of data for complete resolution at more than six months was possible, with an increase in resolution of 13% (RD 0.13, 95% CI 0.06 to 0.19).Pooled analysis was also possible for complete resolution at the end of treatment, with the following increases in resolution rates: 17% (RD 0.17, 95% CI 0.09 to 0.24) for treatment for 10 days to two weeks, 34% (RD 0.34, 95% CI 0.19 to 0.50) for treatment for four weeks, 32% (RD 0.32, 95% CI 0.17 to 0.47) for treatment for three months, and 14% (RD 0.14, 95% CI 0.03 to 0.24) for treatment continuously for at least six months.We were unable to find evidence of a substantial improvement in hearing as a result of the use of antibiotics for otitis media with effusion; nor did we find an effect on the rate of ventilation tube insertion. We did not identify any trials that looked at speech, language and cognitive development or quality of life. Data on the adverse effects of antibiotic treatment reported in six studies could not be pooled due to high heterogeneity. Increases in the occurrence of adverse events varied from 3% (RD 0.03, 95% CI -0.01 to 0.07; not significant) to 33% (RD 0.33, 95% CI 0.22 to 0.44) in the individual studies. The results of our review do not support the routine use of antibiotics for children up to 18 years with otitis media with effusion. The largest effects of antibiotics were seen in children treated continuously for four weeks and three months. Even when clear and relevant benefits of antibiotics have been demonstrated, these must be balanced against the potential adverse effects when making treatment decisions. Immediate adverse effects of antibiotics are common and the emergence of bacterial resistance has been causally linked to the widespread use of antibiotics for common conditions such as otitis media.